Demystifying the Issue of House Affordability in Malaysia: The Bi-Directional Relationship Between House Prices, Economic Growth, and Income Inequality - Saizal Pinjaman; Debbra Toria Nipo; Sarma Aralas (Human Resource Management Academic Research Society, 2023)
To understand the issue of house affordability in Malaysia, this study investigated the relationship between house prices and economic growth based on the data from the year 2000 to 2020. By utilizing the Toda-Yamamoto Granger causality test, it is identified that the relationship between the variables is bidirectional where house price movement is explained by economic growth. It implies that economic development drives house prices upward in the country. Conversely, the level of economic growth is also determined by house prices, and this clarifies the significant role of the housing market in stimulating the economy. The analysis also indicates that there is a mutual interaction between house prices and income inequality. Although the increase in house prices leads to higher economic growth, the rise in aggregate income that comes with it is enjoyed mainly by the top income earners of society. These findings are important for policymakers in addressing the issue of house affordability since it suggests that the issue of house affordability is partly contributed by income disparity. Since house price moves together with economic development, houses in Malaysia should remain affordable as long as income disparity is lessened if not diminished by ensuring that the economic prosperity is equally distributed among the society.